O comércio internacional de tecnologias ambientais: a inserção do Brasil e da China - Nascimento, Renata Muniz do [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This thesis analyzes international trade in environmental technologies between the years 2002 and 2013 with four objectives: (1) analyze the pattern of international trade to verify the hypothesis of the existence of a north-south pattern, in which the member countries of the OECD, represented by developed countries, leading exports and non-OECD countries, represented by developing and least developed countries, practically limited to the status of importers of environmental technologies; (2) to analyze the insertion of Brazil in international trade of environmental technologies, in particular the performance of its trade balance in this segment; (3) in a similar manner and for purposes of comparison with Brazil, analyze the inclusion of China in international trade in environmental technologies; and (4) assess the level of tariff protection on imports of environmental goods in the OECD group compared to the group of non-OECD countries, especially the data of Brazil and China, in order to check whether there was a liberalization of trade in such goods. The results of this study show the maintenance, in aggregate, North-South pattern of international trade in environmental technologies, but the scenery begins to change in China's rise of reason and the US share decline and Japan in this trade. But Brazil has deepened its trade deficit in environmental goods in this period. Regarding the degree of tariff protection, the developed countries have reduced average tariffs of import compared to those applied by developing countries. China keeps an average of very similar to those import tariffs by developing countries. Brazil already applies much higher than average rates of import those practiced by China, which may explain their lack of representation in the international trade of environmental technologies

Esta dissertação analisa o comércio internacional de tecnologias ambientais entre os anos de 2002 e 2013 com quatro objetivos: (1) analisar o padrão de comércio internacional para averiguar a hipótese de existência de um padrão Norte-Sul, em que os países membros da OCDE, representado por países desenvolvidos, lideram as exportações e os países não membros da OCDE, representado por países em desenvolvimento e menos desenvolvidos, praticamente se limitam à condição de importadores de tecnologias ambientais; (2) analisar a inserção do Brasil no comércio internacional de tecnologias ambientais, em especial o desempenho da sua balança de comércio nesse segmento; (3) de modo semelhante e para fins de comparação com o Brasil, analisar a inserção da China no comércio internacional de tecnologias ambientais; e (4) verificar o grau de proteção tarifária sobre a importação de bens ambientais do grupo de países da OCDE comparado ao grupo de países não membros da OCDE, com destaque para os dados do Brasil e da China, a fim de conferir se houve uma liberalização do comércio desses bens. Os resultados deste estudo evidenciam a manutenção, em termos agregados, do padrão Norte-Sul do comércio internacional de tecnologias ambientais, mas o cenário começa a mudar em razão da ascensão da China e do declínio da participação dos EUA e do Japão nesse comércio. Já o Brasil aprofundou o seu déficit comercial em bens ambientais nesse período. No tocante ao grau de proteção tarifária, os países desenvolvidos mantêm tarifas médias de importação reduzidas se comparadas àquelas aplicadas pelos países em desenvolvimento. A China mantém uma média de tarifas de importação muito semelhante àquelas aplicadas pelos países em desenvolvimento. Já o Brasil aplica tarifas médias de importação muito superiores àquelas praticadas pela China, o que pode justificar sua...
Keywords: Comércio internacional; Tecnologia verde; Bens de capital; International trade; Brasil - Comércio - China; China - Comércio - Brasil